2021
DOI: 10.1016/j.jece.2021.105222
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 pandemic and emerging plastic-based personal protective equipment waste pollution and management in Africa

Abstract: The threat of plastic waste pollution in African countries is increasing exponentially since the World Health Organisation declared the coronavirus infection as a pandemic. Fundamental to this growing threat are multiple factors, including the increased public consumption for single-use plastics, limited or non-existence of adequate plastic waste management infrastructures, and urbanisation. Plastics-based personal protective equipment including millions of surgical masks, medical gowns, face shields, safety g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
89
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(92 citation statements)
references
References 45 publications
2
89
0
1
Order By: Relevance
“…Therefore, the results could be overestimated. However, the results of this work are in agreement with other contemporary studies [46]. Consequently, further research is needed to investigate the way in which the Moroccan community uses and manages their used PPE items to establish efficient strategies and policies.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Therefore, the results could be overestimated. However, the results of this work are in agreement with other contemporary studies [46]. Consequently, further research is needed to investigate the way in which the Moroccan community uses and manages their used PPE items to establish efficient strategies and policies.…”
Section: Discussionsupporting
confidence: 87%
“…The difference between each country legislations regarding facemask wearing is the main reason for the variation of countries' communities' behavior over the wearing of masks in public during the COVID-19 pandemic. A recent study [46] showed that if 70% of the Moroccan population wear at least one mask per day, the estimated number of facemasks generated and disposed of daily will be around 16,537,438, equivalent to 140,568 kg of facemasks that could be disposed daily in different environments by people living in Morocco. In the same way, we estimated the total daily generated and disposed facemasks for the two studied regions, and surveyed the population using the following equation [46,47]:…”
Section: The Use Of Personal Protective Equipment (Ppe)mentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, it was shown that in several countries, wastes generated by personal disposal used because of pandemic (as for example facemask) are often discarded in the environment and consequently found in water bodies, as for example in wastewater gullies, inland waterways, and drainage canals. Also, this practice strongly impacts SG 11 ( Benson et al, 2021 ) and SDG 15.…”
Section: Resultsmentioning
confidence: 99%